2011
DOI: 10.1111/j.1468-3083.2011.04078.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of plaque‐type psoriasis with oral CF101: data from an exploratory randomized phase 2 clinical trial

Abstract: CF101 was well tolerated and demonstrated clear evidence of efficacy in patients with moderate to severe plaque psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 26 publications
3
65
0
2
Order By: Relevance
“…Accordingly, CF101 was tested in a phase II, multicenter, randomized, double-blind, dose-ranging, placebo-controlled trial in patients with moderate to severe chronic plaque-type psoriasis. In this study the drug was found to be safe and well tolerated, and the improvement was progressive and linear throughout the period examined (David et al, 2012). As a consequence, CF101 has entered a phase II/III randomized, doubleblind, placebo-controlled, dose-finding study of the efficacy and safety of daily CF101 administered orally in patients with moderate to severe plaque psoriasis (ClinicalTrials.gov).…”
Section: Immune System and Inflammationmentioning
confidence: 99%
“…Accordingly, CF101 was tested in a phase II, multicenter, randomized, double-blind, dose-ranging, placebo-controlled trial in patients with moderate to severe chronic plaque-type psoriasis. In this study the drug was found to be safe and well tolerated, and the improvement was progressive and linear throughout the period examined (David et al, 2012). As a consequence, CF101 has entered a phase II/III randomized, doubleblind, placebo-controlled, dose-finding study of the efficacy and safety of daily CF101 administered orally in patients with moderate to severe plaque psoriasis (ClinicalTrials.gov).…”
Section: Immune System and Inflammationmentioning
confidence: 99%
“…In addition, this receptor subtype could be involved in the murine imiquimod-induced model of psoriasis, because imiquimod has been also characterized as an A 2A AR antagonist (Flutter and Nestle, 2013;Schon et al, 2006). Furthermore, an A 3 AR agonist is currently being evaluated in phase II and III clinical trials in patients with moderate to severe plaque psoriasis because of its regulatory effect on T-cell function (David et al, 2012;Kofoed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A supporting factor for this conclusion comes also from the fact that meloxicam is already in clinical use for other indications. IB-MECA is under clinical studies (for other indications, too) in which it was found to be safe and well tolerated [34][35][36].…”
Section: Discussionmentioning
confidence: 99%